Outcomes of Liver Transplantation in Small Infants. Issue 10 (20th September 2019) - Yamamoto, Hidekazu; Khorsandi, Shirin E.; Cortes‐Cerisuelo, Miriam; Kawano, Yoichi; Dhawan, Anil; McCall, John; Vilca‐Melendez, Hector; Rela, Mohamed; Heaton, Nigel
Abstract : Liver transplantation (LT) for small infants remains challenging because of the demands related to graft selection, surgical technique, and perioperative management. The aim of this study was to evaluate the short‐term and longterm outcomes of LT regarding vascular/biliary complications, renal function, growth, and patient/graft survival in infants ≤3 months compared with those of an age between >3 and 6 months at a single transplant center. A total of 64 infants ≤6 months underwent LT and were divided into 2 groups according to age at LT: those of age ≤3 months (range, 6‐118 days; XS group, n = 37) and those of age >3 to ≤6 months (range, 124‐179 days; S group, n = 27) between 1989 and 2014. Acute liver failure was the main indication for LT in the XS group (n = 31, 84%) versus S (n = 7, 26%). The overall incidence of hepatic artery thrombosis and portal vein thrombosis/stricture were 5.4% and 10.8% in the XS group and 7.4% and 11.1% in the S group, respectively (not significant). The overall incidence of biliary stricture and leakage were 5.4% and 2.7% in the XS group and 3.7% and 3.7% in the S group, respectively (not significant). There was no significant difference between the 2 groups in terms of renal function. No significant difference was found between the 2 groups for each year after LT in terms of height and weight z score. The 1‐, 5‐, and 10‐year patient survival rates were 70.3%, 70.3%, and 70.3% in the XS group compared with 92.6%, 88.9%, and 88.9% in the S group, respectively (not significant). In conclusion, LT for smaller infants has acceptable outcomes despite the challenges of surgical technique, including vascular reconstruction and graft preparation, and perioperative management.